PHONETIC REPETITIONS IN THE POETRY OF HAMID OLIMJON - Shofqorov A. M. (Western European Studies, 2024)
The article describes the specific semantic and stylistic features of phonetic repetition in the poetry of Hamid Olimjon. There are also comments on the study of Uzbek linguistics
Keywords: repetition; artistic repetition; phonetic repetition